2020
DOI: 10.1101/2020.04.29.067751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Behavioral Association Between Prediction Errors and Risk-Seeking: Theory and Evidence

Abstract: 9Reinforcement learning theories propose that humans choose based on the estimated values of 10 available options, and that they learn from rewards by reducing the difference between the experienced 11 and expected value. In the brain, such prediction errors are broadcasted by dopamine. However, choices 12 are not only influenced by expected value, but also by risk. Like reinforcement learning, risk preferences 13 are modulated by dopamine: enhanced dopamine levels induce risk-seeking. Learning and risk 14 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, it has been recently demonstrated that even a brief, burst-like activation of dopaminergic neurons changes the activity levels of striatal neurons (31). Additionally, it has been shown that reward prediction errors modulate the tendency to make risky choices (22), and risk attitudes are known to depend on the balance between the direct and indirect pathways (32, 33). In this paper, we demonstrated that a more realistic assumption, that the dopamine signal encoding prediction error also changes the activity levels in striatum, enables scaling of prediction errors by uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been recently demonstrated that even a brief, burst-like activation of dopaminergic neurons changes the activity levels of striatal neurons (31). Additionally, it has been shown that reward prediction errors modulate the tendency to make risky choices (22), and risk attitudes are known to depend on the balance between the direct and indirect pathways (32, 33). In this paper, we demonstrated that a more realistic assumption, that the dopamine signal encoding prediction error also changes the activity levels in striatum, enables scaling of prediction errors by uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…In Eq. 7 and 8, 𝐺 and 𝑁 denote the synaptic inputs in the direct and indirect pathway respectively (22), and 𝜆 is a coefficient determining the accuracy with which the standard deviation can be encoded (as explained below). These assumptions can be used to rewrite the learning rules given in Eq.…”
Section: The Spe Learning Rules Are Consistent With Striatal Plasticitymentioning
confidence: 99%